An oxygen slow-releasing material and its application in water remediation as oxygen supplier. Issue 22 (17th November 2017) - Zhou, Yanbo; Fang, Xingbin; Zhang, Zhiqing; Hu, Yonghua; Lu, Jun
ABSTRACT: In this study, an oxygen slow-releasing material (OSRM) consisting of calcium peroxide (CaO2 ), stearic acid (SA) and quartz sand was used to improve oxygen supply during bioremediation. The oxygen-releasing rates of CaO2 powder and OSRM with different SA contents were investigated. The efficacy of OSRM as an oxygen supplier was assessed by water remediation experiments using activated sludge. Results showed that CaO2 powder was effectively embedded by SA under anhydrous conditions. The oxygen-releasing rate decreased with increasing SA contents. Moreover, the OSRM exhibited higher oxygen-releasing capacity, and more effective pH control ability than CaO2 powder. The water remediation experiments showed better removal of COD and with OSRM as the oxygen supplier. These results provided detailed information when CaO2 was applied as the oxygen supplier in water remediation, which can serve as references for field application of bioremediation.